2010
DOI: 10.1007/s00586-010-1341-x
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral body stenting: a new method for vertebral augmentation versus kyphoplasty

Abstract: Vertebroplasty and kyphoplasty are well-established minimally invasive treatment options for compression fractures of osteoporotic vertebral bodies. Possible procedural disadvantages, however, include incomplete fracture reduction or a significant loss of reduction after balloon tamp deflation, prior to cement injection. A new procedure called “vertebral body stenting” (VBS) was tested in vitro and compared to kyphoplasty. VBS uses a specially designed catheter-mounted stent which can be implanted and expanded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
134
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 21 publications
0
134
1
2
Order By: Relevance
“…However, a significant loss of the restored height after balloon deflation prior to cement injection is a major disadvantage of percutaneous kyphoplasty. Recent studies have shown that the initial reduction achieved by the balloon is mostly lost after deflation [10], because the cavity created partially collapses before the bone cement can be injected [11]. Therefore, the expected spinal re-alignment cannot be completely achieved using percutaneous kyphoplasty [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, a significant loss of the restored height after balloon deflation prior to cement injection is a major disadvantage of percutaneous kyphoplasty. Recent studies have shown that the initial reduction achieved by the balloon is mostly lost after deflation [10], because the cavity created partially collapses before the bone cement can be injected [11]. Therefore, the expected spinal re-alignment cannot be completely achieved using percutaneous kyphoplasty [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed during balloon kyphoplasty procedures that vertebral height restored during inflation of the bone tamp can be lost after balloon deflation due to elastic recoil of the vertebral body. This has been demonstrated in an in vitro study where anterior height loss was significantly higher in balloon kyphoplasty compared with vertebral body stenting (VBS): 12 versus 4 %, respectively (p = 0.003) [9]. Both kyphoplasty and VBS rely on balloon-assisted vertebral fracture reduction methods.…”
Section: Discussionmentioning
confidence: 86%
“…A comparative trial involving balloon kyphoplasty and a titanium implant was performed in a biomechanical in vitro study [9]. Significantly greater vertebral height loss (p \ 0.025) was detected after reconstruction with kyphoplasty repair compared with the titanium mesh implant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations